Laser-induced excited-state crossover and spectral variation of Cr3+ in the high-crystal-field environment of CaGa2O4 - Rai M.; Singh S.K.; Morthekai P. (My University, 2025)
We have studied a wide-bandgap oxide semiconductor, CaGa1.99Cr0.01O4, which possesses high crystal field strength and develops deep traps. These traps efficiently store electric charges after excitation with ultraviolet light. Stimulation of trap charges using infrared radiation (both coherent and incoherent) gives wideband emission of Cr3+ in the red-infrared region, which is similar to the photon upconversion process in lanthanides. Under laser excitation, high photon density and local heating pronounce the coupling of 2E and 4T2 states and causes an excited state crossover of the population from the 2E to 4T2 state. This expands the emission band-width of Cr3+ up to 900 nm. © 2016 Optical Society of America.